2016
DOI: 10.1007/978-1-4939-4002-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Constipation and Herbal Medicine

Abstract: Citation:Iizuka N and Hamamoto Y (2015) Constipation and herbal medicine.Front. Pharmacol. 6:73. doi: 10.3389/fphar.2015.00073 Constipation is characterized by a variety of bowel symptoms such as difficulty passing stool, hard stool, and a feeling of incomplete evacuation. The multifactorial causes of constipation limit the clinical efficacy of current conventional treatments that use a single drug that acts through only one pathway. To complement the shortcomings of the current Western medical model an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 56 publications
1
15
0
1
Order By: Relevance
“…Second, some physical side effects caused by antipsychotics can be relieved by Kampo formulae. For example, Kampo formula containing rhubarb improves constipation [39]. A randomized, double-blind study indicated that Mashiningan improved bowel movement (Mashiningan, n = 60; placebo, n = 60) (p < 0.05) and re-…”
Section: Schizophrenia Spectrum Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, some physical side effects caused by antipsychotics can be relieved by Kampo formulae. For example, Kampo formula containing rhubarb improves constipation [39]. A randomized, double-blind study indicated that Mashiningan improved bowel movement (Mashiningan, n = 60; placebo, n = 60) (p < 0.05) and re-…”
Section: Schizophrenia Spectrum Disordersmentioning
confidence: 99%
“…Hangekobokuto is considered to modulate cerebral levels of 5-hydroxytryptamine, noradrenaline, dopamine, and substance-P, the last of which could improve swallowing function [56,73]. Keishikashakuyakuto is the most frequently investigated Kampo formula for the treatment of irritable bowel syndrome (IBS) [39,[74][75][76].…”
Section: Anxiety Disorders Stress-related Disorders and Somatoform mentioning
confidence: 99%
“…27,28 The pharmacologic effects of rhubarb are due to its active constituents of anthraquinone glycosidesspecifically, rheinanthrone, aloe-emodin, and physcion. 29 These compounds exert therapeutic effects that stimulate peristalsis of the GI tract 28,30 and may alleviate constipation. 30,31 Anthraquinones found in rhubarb are found in other stimulant laxatives.…”
Section: Rhubarb For Constipation and Gi Motilitymentioning
confidence: 99%
“…29 These compounds exert therapeutic effects that stimulate peristalsis of the GI tract 28,30 and may alleviate constipation. 30,31 Anthraquinones found in rhubarb are found in other stimulant laxatives. 32 As EN becomes an increasingly more integral component of patient care, improvements in the prevention of aspiration and constipation, via improved gastric motility, warrant close attention.…”
Section: Rhubarb For Constipation and Gi Motilitymentioning
confidence: 99%
“…Keishi ka shakuyaku tō (KST) ist ein in Japan häufig bei Reizdarmsyndrom (RDS) verwendetes und hinsichtlich seiner wirksamen Bestandteile intensiv beforschtes Phytopharmakon [21,22]. Die Rezeptur setzt sich aus 5 Einzeldrogen zusammen: Paeoniae radix (6,0 g), Cinnamomi cortex (4,0 g), Zizyphi fructus (4,0 g), Glycyrrhizae radix (2,0 g) und Zingiberis rhizoma (1,0 g).…”
Section: Reizdarmsyndrom: Keishi Ka Shakuyaku Tōunclassified